eCM 2016
DOI: 10.22203/ecm.v031a26
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells from human umbilical cords display poor chondrogenic potential in scaffold-free three dimensional cultures

Abstract: Many researchers world over are currently investigating the suitability of stromal cells harvested from foetal tissues for allogeneic cell transplantation therapies or for tissue engineering purposes. In this study, we have investigated the chondrogenic potential of mesenchymal stromal cells (MSCs) isolated from whole sections of human umbilical cord or mixed cord (UCSCs-MC), and compared them with cells isolated from synovial membrane (SMSCs), Hoffa's fat pad (HFPSCs) and cartilage. All MSCs were positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Macroscopically-normal-looking cartilage, corresponding to cartilage areas looking intact to the eye and presenting no signs of abnormalities, such as tears, scratches, rugose or eroded tissue, was collected from femoral condyles during total knee replacements and was used to isolate human chondrocytes. All cell types were isolated using a mixed enzymatic-explant method, as previously described (Islam et al, 2016;Islam et al, 2017). Briefly, all tissue specimens were washed three times with sterile Dulbecco's phosphate buffered saline (PBS; D8537, Sigma-Aldrich) and minced into small pieces for subsequent enzymatic digestion in collagenase XI solution (≥ 800 units/mg solid; C9407, Sigma-Aldrich) at a final concentration of 1.25 mg/mL at 37 °C on a shaker at 400 rpm.…”
Section: Isolation and Culture Of Human Stromal Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Macroscopically-normal-looking cartilage, corresponding to cartilage areas looking intact to the eye and presenting no signs of abnormalities, such as tears, scratches, rugose or eroded tissue, was collected from femoral condyles during total knee replacements and was used to isolate human chondrocytes. All cell types were isolated using a mixed enzymatic-explant method, as previously described (Islam et al, 2016;Islam et al, 2017). Briefly, all tissue specimens were washed three times with sterile Dulbecco's phosphate buffered saline (PBS; D8537, Sigma-Aldrich) and minced into small pieces for subsequent enzymatic digestion in collagenase XI solution (≥ 800 units/mg solid; C9407, Sigma-Aldrich) at a final concentration of 1.25 mg/mL at 37 °C on a shaker at 400 rpm.…”
Section: Isolation and Culture Of Human Stromal Cellsmentioning
confidence: 99%
“…In vitro 3D chondrogenic assays of dedifferentiated chondrocytes was performed using a pellet culture method as described previously (Islam et al, 2016). Briefly, chondrocytes were harvested at P3, centrifuged in a conical-bottom 96-well plate for 10 min at 1,100 ×g and incubated in culture medium for 48 h in low oxygen (3 % O 2 ) atmosphere.…”
Section: Three-dimensional (3d) Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…In three-dimensional cultures, cultivated for 3 to 4 weeks in chondrogenic medium supplemented or not with growth factors (such as transforming growth factor (TGF)-β1 and TGF-β3), several groups including our own reported that WJ-MSC showed chondrogenic induction with expression of specific cartilage-related genes and matrix proteins (Sox9, proteoglycans, type 2 collagen, cartilage oligomeric matrix protein (COMP)) [4, 11, 2426]. However, a recent study was more reserved, showing poor chondrogenesis from MSC isolated from umbilical cord [27]. …”
Section: Introductionmentioning
confidence: 99%